Research and Practice of Online Course Design of Cross-border E-commerce or Application-oriented Undergraduate - WANG, Ni; YANG, Xi; LUO, Ming (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
As we all know that cross-border e-commerce has become a new highlight in the growth of foreign trade for the past years, while higher requirements are put forward to the quality of talents in this field. Now, Internet online education model is in a rising period of development in China, and the construction of online course supported by Internet and modern information technology is an important direction of current classroom teaching reform. In this paper, the preliminary framework of online course design of Cross-border E-commerce is mainly discussed to adapt to this trend and cultivate the interdisciplinary application-oriented undergraduate talents specialized in cross-border e-commerce required by the industry.